Reliable communications over lossy wireless channels by means of the combination of UDP and Random Linear Coding - Gomez, David; Rodriguez, Eduardo; Aguero, Ramon; Munoz, Luis (Proceedings - IEEE Symposium on Computers and Communications, 2014)
It goes without saying that TCP is the de-facto transport protocol to ensure reliable communications (for instance, in file transfers). On the other hand, and despite the growing relevance of wireless networks, the behavior of TCP over such technologies is well-known to present clear limitations. Several approaches have been made so as to overcome these problems. In this work we propose a different approach to ensure reliable transmissions over wireless links, based on an Random Linear Coding (RLC) scheme, operating together with UDP. We provide a model of the expected performance of the new scheme. Furthermore, based on an extensive simulation campaign over the ns-3 simulation framework, we assess the validity of this model and we compare its performance with that exhibited by the legacy TCP. The results show that, in particular for lossy links, the proposed scheme clearly outperforms TCP.